Legal, scientific, informational and ideological measures to ensure sustainable use of wild life objects: russian andforeign experience - Ivanova, Svetlana (DIXI, 2023)
This article deals with the ecological education as an important means in the process of animal world preservation. Legal education is supposed to form a high level of legal awareness and legal culture among citizens and society. The result of legal education should be regarded in knowledge, citizens’ respectful attitude to the current legislation. According to this article, a high level of legal culture and legal education will allow everyone to realize the need to preserve the biodiversity of wild animals for the present and future generations. Based on the analysis of certain provisions of the legislation on the animal world and law enforcement practice, the article states that there is no comprehensive system of legal measures for the sustainable use of wildlife in Russia. The legal, economic, ideological, organizational measures proposed in this article will make it possible to achieve such use of the animal world that will preserve and increase the number of wild animal populations, maintain ecological balance, and ensure satisfaction of the needs of present and future generations in a favorable environment. The measures proposed will create a legal basis for sustainable management of the animal world. These measures will be useful in the development of national programs for the sustainable use of wildlife, strengthening the dialogue of the authorities with the population to involve them in the process of sustainable use of wildlife objects in order to ensure a balance of economic, environmental and social interests.
Keywords: Conservation; conservation of animal world biodiversity; ecological balance; ecological education; legal culture; legal support measures; public and private interests